2021
DOI: 10.1038/s41598-021-83227-8
|View full text |Cite
|
Sign up to set email alerts
|

Faceted-rough surface with disassembling of macrosteps in nucleation-limited crystal growth

Abstract: To clarify whether a surface can be rough with faceted macrosteps that maintain their shape on the surface, crystal surface roughness is studied by a Monte Carlo method for a nucleation-limited crystal-growth process. As a surface model, the restricted solid-on-solid (RSOS) model with point-contact-type step–step attraction (p-RSOS model) is adopted. At equilibrium and at sufficiently low temperatures, the vicinal surface of the p-RSOS model consists of faceted macrosteps with (111) side surfaces and smooth te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…In our previous work regarding the step-faceting zone in the non-equilibrium steady state 22 , 26 , 55 , we showed that the mean height of a faceted macrostep for in the step-faceting zone is sensitive to the initial configuration. Here, represents the bulk chemical difference between the crystal and the ambient phases, represents a crossover point between the 2D single nucleation and the poly-nucleation processes at the edge of the faceted macrosteps, and L is the linear size of the system.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous work regarding the step-faceting zone in the non-equilibrium steady state 22 , 26 , 55 , we showed that the mean height of a faceted macrostep for in the step-faceting zone is sensitive to the initial configuration. Here, represents the bulk chemical difference between the crystal and the ambient phases, represents a crossover point between the 2D single nucleation and the poly-nucleation processes at the edge of the faceted macrosteps, and L is the linear size of the system.…”
Section: Resultsmentioning
confidence: 88%
“…We found zipping phenomena 50 and pinning phenomena 51 , 56 . At a slope of , we observed disassembling/assembling of faceted macrosteps 22 , 25 , 26 and a faceted rough surface 55 between the atomically rough and thermodynamic rough surfaces. From the slope dependence of the surface width, which is the standard deviation of the surface height, in the RSOS model ( ), the roughness exponent near (001) is different from that near (111) for large 35 .…”
Section: Discussionmentioning
confidence: 95%
“…With all due caution, namely the difference of Péclet number and growth regime (diffusion limited growth versus slow growth), origin of growth anisotropy (capillary versus kinetic), as well as the peculiarities of smooth and rough faceting [49], the presently described mechanism for ISB might provide an alternative scenario for the sprouting of side branches in snowflake as was experimentally observed upon changing growth conditions in [30]. In his book, Libbrecht ascribes ISB to a purely morphological origin.…”
Section: Discussionmentioning
confidence: 99%
“…With all due caution, namely the difference of Péclet number and growth regime (diffusion limited growth vs. slow growth), origin of growth anisotropy (capillary vs. kinetic), as well as the peculiarities of smooth and rough faceting [46], the presently described mechanism for ISB might provide an alternative scenario for the sprouting of side branches in snowflake as was experimentally observed upon changing growth conditions in [31]. In his book, Libbrecht ascribes ISB to a purely morphological origin.…”
Section: Discussionmentioning
confidence: 99%